Systematic review of multidrug-resistant Klebsiella pneumoniae in the Arabian Peninsula: molecular epidemiology and resistance patterns - Idrees, Enaam K.; Aldriwesh, Marwh G.; Alkhulaifi, Manal M.; Alghoribi, Majed F. (Frontiers in Microbiology, 2025)
BackgroundThe rapid emergence of multidrug-resistant Klebsiella pneumoniae (MDR K. pneumoniae) is a major public health and economic burden worldwide. Various resistance mechanisms complicate treatment, leading to increased morbidity and mortality. Despite numerous studies conducted in Gulf Health Council (GHC) countries, the molecular epidemiology of MDR K. pneumoniae remains not clearly defined. This systematic review aims to analyze the emergence of antimicrobial resistance genes in MDR K. pneumoniae across GHC countries.MethodsA systematic search was conducted using PubMed, ScienceDirect, and OpenMD for articles published up to March 15, 2023. The search strategy focused on the bacterial name, drug-resistance genotypes, and GHC countries. The review followed PRISMA guidelines, with two independent reviewers assessing the risk of bias using NIH Study Quality Assessment tools.ResultsThe primary search yielded 1,663 studies, of which 67 met the inclusion criteria. Saudi Arabia contributed the most studies, with 41 (61.1%), followed by Kuwait with 7 (10.4%), and the UAE with 6 (9%) studies. Oman and Qatar each contributed 4 studies (6%), and Bahrain contributed three studies (4.5%). The remaining 4 studies (4.4%) were from multiple GHC countries. The studies exhibited considerable heterogeneity in detection methods, target genes, and resistance mechanisms. Notably, only one environmental study was conducted in the UAE, and one community-based study in Kuwait, while the remaining studies focused on clinical samples. Various resistance mechanisms and patterns were observed between countries and across different years within the same country. The review highlighted the widespread prevalence of ESBL genes, particularly blaTEM and blaCTX-M-15, and the emergence of carbapenemase genes such as blaOXA-48 and blaNDM-1 and blaKPC-2. Additionally, colistin resistance through the mcr-1 gene and mgrB mutations was reported in Saudi Arabia and the UAE, posing a significant public health challenge.ConclusionData from GHC countries shows significant gaps, particularly in community and environmental and molecular epidemiology studies. Limited molecular and genome-based investigations hinder comprehensive AMR surveillance. Implementing standardized methodologies and fostering molecular and genome-based AMR surveillance programs at both national and regional levels within the GHC are essential for effectively combating the spread of MDR K. pneumoniae and improving public health outcomes in the region.